p=2a+2b

Rewrite the equation as 2a+2b=p.

2a+2b=p

Subtract 2b from both sides of the equation.

2a=p-2b

Divide each term in 2a=p-2b by 2.

2a2=p2+-2b2

Cancel the common factor of 2.

Cancel the common factor.

2a2=p2+-2b2

Divide a by 1.

a=p2+-2b2

a=p2+-2b2

Cancel the common factor of -2 and 2.

Factor 2 out of -2b.

a=p2+2(-b)2

Cancel the common factors.

Factor 2 out of 2.

a=p2+2(-b)2(1)

Cancel the common factor.

a=p2+2(-b)2⋅1

Rewrite the expression.

a=p2+-b1

Divide -b by 1.

a=p2-b

a=p2-b

a=p2-b

a=p2-b

Solve for a p=2a+2b